2017
DOI: 10.1007/s00253-017-8535-7
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori treatment: antibiotics or probiotics

Abstract: Treatment of Helicobacter pylori infection is important for the management of gastrointestinal disorders such as peptic ulcer and gastric cancer. Due to the increase in the prevalence of H. pylori resistance to antibiotics, triple therapy with clarithromycin is no longer the best treatment for H. pylori, especially in some areas where the local resistance to this antibiotic is higher than 20%. Alternative treatments have been proposed for the eradication of H. pylori. Some of them including novel antibiotics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
206
1
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(223 citation statements)
references
References 63 publications
2
206
1
14
Order By: Relevance
“…Different strains of the lactic acid bacteria (LAB), and particularly some Lactobacillus spp., are representing some of the most commonly used probiotics, defined as "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host" (Food and Agriculture Organization [FAO], and World Health Organization [WHO], 2002). Extensive research has been performed on the efficacy of various Lactobacillus strains on gastric ulcers (Dharmani et al, 2013;Khoder et al, 2016) either as single therapeutic agents or in combination with antibiotics (Boltin, 2016;Goderska et al, 2018). The majority of the investigated strains have been shown to inhibit or protect the gastric mucosal barrier through the up-regulation of prostaglandin E2 (Uchida and Kurakazu, 2004;Gotteland et al, 2006;Lam et al, 2007;Uchida et al, 2010), enhancement of mucus secretion (Gomi et al, 2013) or the regulation of inflammatory responses (Konturek et al, 2009;Şenol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different strains of the lactic acid bacteria (LAB), and particularly some Lactobacillus spp., are representing some of the most commonly used probiotics, defined as "live microorganisms which, when administered in adequate amounts, confer a health benefit on the host" (Food and Agriculture Organization [FAO], and World Health Organization [WHO], 2002). Extensive research has been performed on the efficacy of various Lactobacillus strains on gastric ulcers (Dharmani et al, 2013;Khoder et al, 2016) either as single therapeutic agents or in combination with antibiotics (Boltin, 2016;Goderska et al, 2018). The majority of the investigated strains have been shown to inhibit or protect the gastric mucosal barrier through the up-regulation of prostaglandin E2 (Uchida and Kurakazu, 2004;Gotteland et al, 2006;Lam et al, 2007;Uchida et al, 2010), enhancement of mucus secretion (Gomi et al, 2013) or the regulation of inflammatory responses (Konturek et al, 2009;Şenol et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, not only do these probiotics have prophylactic effects, but some of them also exert therapeutic effects through the enhancement of epithelial growth (Singh and Kaur, 2012), promotion of angiogenesis (Dharmani et al, 2013) and up-regulation effect on anti-inflammatory cytokines expression (Virchenko et al, 2015). Currently, approaches involving therapies either with "new" antimicrobials and/or probiotics are considered promising approaches for therapeutics or prophylactics of gastric ulcers (Goderska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The potential molecular mechanism may be involved in the anti-oxidative and anti-inflammatory activities which are able to protect the gastric mucosa, suppress the inflammatory and immune response and rebalance the micro ecosystem after Hp infection [11]. Seen from this, the combination of probiotics and the standard Hp eradication regimen may improve the Hp eradication rate [12].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriocins, mainly produced by Lactobacillus , Enterococcus , and Brevibacillus spp ., are small peptidic structures with antimicrobial properties (Goderska, Pena, & Alarcon, ; Hanchi, Mottawea, Sebei, & Hammami, ). Gaspar et al () found that a bacteriocin natively produced by L. acidophilus KS400 could inhibit the growth of vaginal pathogenic microorganisms, including Gardnerella vaginalis , Streptococcus agalactiae , and Pseudomonas aeruginosa (Gaspar et al, ).…”
Section: Antimicrobial Activity Of Probioticsmentioning
confidence: 99%